Off-label use of tocilizumab to treat non-juvenile idiopathic arthritis in pediatric rheumatic patients: a literature review - Ju-Yang Jung; Moon-Young Kim; Chang-Hee Suh; Hyoun-Ah Kim (BMC, 2018)
Abstract Tocilizumab, an anti-interleukin-6 (IL-6) agent, is indicated as a treatment for several autoimmune or inflammatory diseases, including rheumatoid arthritis and juvenile idiopathic arthritis (JIA). IL-6 plays roles in both immune system dysregulation and inflammation, and thus efforts to extend the utility of tocilizumab in patients with autoinflammatory conditions are ongoing. Here, we survey the literature on the off-label use of tocilizumab in patients with juvenile-onset rheumatic diseases including juvenile systemic lupus erythematosus (SLE), juvenile dermatomyositis (DM), vasculitis, juvenile scleroderma, and other autoinflammatory diseases. There is no real evidence that tocilizumab is useful for patients with SLE and juvenile DM, but several cases of childhood Takayasu arteritis have experienced promising outcomes. In juvenile-onset scleroderma, for which no therapy that can halt disease progression is available, tocilizumab may stop progression and the associated functional impairment. Tocilizumab prevents systemic inflammation in patients with Kawasaki's disease, but may develop coronary aneurysms. Tocilizumab has been used to treat several pediatric autoinflammatory diseases, including JIA-associated uveitis and Castleman's disease. Further work in larger populations is necessary to confirm the effects of tocilizumab in patients with pediatric rheumatic diseases.